Activation of CNR1/PI3K/AKT Pathway by Tanshinone IIA Protects Hippocampal Neurons and Ameliorates Sleep Deprivation-Induced Cognitive Dysfunction in Rats - Li, Zi-Heng; Cheng, Li; Wen, Chun; Ding, Li; You, Qiu-Yun; Zhang, Shun-Bo (Frontiers in Pharmacology, 2022)
Sleep deprivation is commonplace in modern society，Short periods of continuous sleep deprivation(SD) may negatively affect brain and behavioral function and may lead to vehicle accidents and medical errors. Tanshinone IIA (Tan IIA) is an important lipid-soluble component of Salvia miltiorrhiza, which could exert neuroprotective effects。The aim of this study was to investigate the mechanism of neuroprotective effect of Tan IIA on acute sleep deprivation-induced cognitive dysfunction in rats. Tan IIA ameliorated behavioral abnormalities in sleep deprived rats, enhanced behavioral performance in WMW and NOR experiments, increased hippocampal dendritic spine density, and attenuated atrophic loss of hippocampal neurons. Tan IIA enhanced the expression of CNR1, PI3K, AKT, STAT3 in rat hippocampus and down-regulated the expression ratio of Bax to Bcl-2. These effects were inhibited by cannabinoid receptor 1 antagonist (AM251). In conclusion, Tan IIA can play a neuroprotective role by activating the CNR1/PI3K/AKT signaling pathway to antagonize apoptosis in the hippocampus and improve sleep deprivation-induced spatial recognition and learning memory dysfunction in rats. Our study suggests that Tan IIA may be a candidate for the prevention of sleep deprivation-induced dysfunction in spatial recognition and learning memory.